Adalimumab biosimilars, ABP501 and SB5, are equally effective and safe as adalimumab originator - Linda Cingolani (Nature Portfolio, 2021)
Abstract To date, data on effectiveness and safety of Adalimumab (ADA) biosimilars in inflammatory bowel diseases (IBDs) are lacking. Therefore, we aimed to verify the ability of ABP501 and SB5 to maintain the clinical and biochemical response induced by the ADA originator, after switching to them. We prospectively analyzed data collected from 55 patients with IBD who switched to ABP501, and 25 patients with IBD who switched to SB5, from ADA originator at four IBD Units between 2018 and 2020. In addition, we included an age and sex-matched control group (n = 38) who continued ADA originator for at least two years and who did not switch to a biosimilar drug. Clinical and biochemical data (C-Reactive Protein (CRP), fecal calprotectin (FC)), concomitant steroid and/or immunosuppressant therapy at the time of the switch and after six months were collected. At six months, in the ABP501 group, we did not observe statistically significant modifications in clinical activity of disease (p = 0.09) and FC values (p = 0.90). Some patients (n = 8) needed to add steroids at six months after switching (p = 0.01), however the need for optimization was not significant between the two timepoints (p = 0.70). Finally, 14.5% patients stopped therapy after six months. Similarly, in the SB5 group we observed a stability of clinical activity and FC values (p = 0.90 and p = 0.20), and a concomitant statistically significant decrease in CRP (p = 0.03). There were no differences in steroids/immunosuppressants need or optimizing biological therapy in this group. Finally, drug survival curves of patients who switched from originator to ABP501 and those who continued ADA originator were similar (p = 0.20). Overall, biosimilar drugs seem to be as effective and safe as the originator. Further larger and longer studies are mandatory to understand the clinical implications of these findings.